Warplanes of the Luftwaffe - 20160731 frey50; Donald, David (London : Aerospace Pub. ; Westport, CT, USA : AIRtime Pub., 1994)
Book illustrated with photos and cutaways of all types of German aircraft form the Second World War.
Includes index.
80311
Keywords: Germany. -- Luftwaffe -- Equipment -- History; Germany. -- Luftwaffe; Airplanes, Military -- Germany -- History; World War, 1939-1945 -- Equipment and supplies; Military aircraft -- History; Germany